Stem cells and their application in dentistry: A review - Muraleedhara Bhat; Praveen Shetty; Subramanya Shetty; Faizan A Khan; Shabeeb Rahman; Mallikarjuna Ragher (Wolters Kluwer Medknow Publications, 2019)
The use of the term "stem cells" dates back to the 1800s; however, the application of the same is still not completely understood. Recent advances have indicated the harvesting of postnatal stem cells from sources such as the dental pulp and fat. The pluripotent nature of these cells allows for use in various aspects of treatment and patient care such as organ and tissue transplantation, bony defects repair, distraction osteogenesis, cell therapies, gene therapy, and toxicology testing of new drugs. This article explores the various aspects involved, the current status, and future challenges of stem cell therapy in patient care and management.